Portrayal of Rohingya People: Discourse Structure Analysis - Puspita Sari, Lydia; Indarti, Yulia (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to reveal the portrayal of Rohingya people, in an article entitled “Myanmar Troops Systematically Gang-Raped Rohingya Women: a UN Envoy”, published in The Jakarta Post. By applying qualitative approach to describe how language is utilized to portray Rohingya people, the data of this study were received from the official website of The Jakarta Post. The news article comprises two broad levels of discourse structure, which are global structures and local structure. The global structures analyze the global topic and the global schema  of the news report. The second level is the local structure or microstructure.